Amyloid assembly endows gad m 1 with biomineralization properties - Castellanos, M.; Torres-Pardo, A.; Rodríguez-Pérez, R.; Gasset, M. (Biomolecules, 2018)
Acid proteins capable of nucleating Ca and displaying aggregation capacity play key roles in the formation of calcium carbonate biominerals. The helix-loop helix EF-hands are the most common Ca-binding motifs in proteins. Calcium is bound by the loop region. These motifs are found in many proteins that are regulated by calcium. Gad m 1, an Atlantic cod β-parvalbumin isoform, is a monomeric EF-hand protein that acts as a Ca buffer in fish muscle; the neutral and acid apo-forms of this protein can form amyloids. Since Ca-nucleating proteins have a propensity to form extended β-strand structures, we wondered whether amyloid assemblies of an EF-hand protein were able to influence calcium carbonate crystallization in vitro. Here, we used the Gad m 1 chain as a model to generate monomeric and amyloid assemblies and to analyze their effect on calcite formation in vitro. We found that only amyloid assemblies alter calcite morphology. Peer Reviewed